1994
DOI: 10.1007/bf03188920
|View full text |Cite
|
Sign up to set email alerts
|

The design of potential antidiabetic drugs: experimental investigation of a number of β-D-glucose analogue inhibitors of glycogen phosphorylase

Abstract: alpha-D-glucose is a weak inhibitor (Ki = 1.7 mM) of glycogen phosphorylase (GP) and acts as physiological regulator of hepatic glycogen metabolism; it binds to GP at the catalytic site and stabilizes the inactive T state of the enzyme promoting the action of protein phosphatase 1 and stimulating glycogen synthase. The three-dimensional structures of T state rabbit muscle GPb and the GPb-alpha-D-glucose complex have been exploited in the design of better regulators of GP that could shift the balance between gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
2

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 11 publications
1
13
0
2
Order By: Relevance
“…a K , of 32 pM, a value that is 50-fold lower than the corresponding K , of 1.7 mM for a-D-glucose or 250-fold lower than the corresponding value of 7.4 mM for the parent (3-D-glucose (Martin et al, 1991;Oikonomakos et al, 1994), and a Hill coefficient n = 1.6, with respect to Glc-1-P, is one of the best T-state inhibitors of phosphorylase b. Comparison of inhibition constants indicates differences in binding energies between 1-GlcNAc and a-D-glucose, and 1-GlcNAc and (3-D-glucose of about 2.4 and 3.3 kcal/mol, respectively.…”
Section: Van Der Waals Contacts For I-glcnac Atoms In the Phosphorymentioning
confidence: 76%
“…a K , of 32 pM, a value that is 50-fold lower than the corresponding K , of 1.7 mM for a-D-glucose or 250-fold lower than the corresponding value of 7.4 mM for the parent (3-D-glucose (Martin et al, 1991;Oikonomakos et al, 1994), and a Hill coefficient n = 1.6, with respect to Glc-1-P, is one of the best T-state inhibitors of phosphorylase b. Comparison of inhibition constants indicates differences in binding energies between 1-GlcNAc and a-D-glucose, and 1-GlcNAc and (3-D-glucose of about 2.4 and 3.3 kcal/mol, respectively.…”
Section: Van Der Waals Contacts For I-glcnac Atoms In the Phosphorymentioning
confidence: 76%
“…After extensive washes of the hepatocytes, counts released into the medium will mainly be a mixture of [U-"%C]glucose, [U-"%C] lactate and, to a minor extent, other carbon-containing metabolites [25]. The amount of glucose and lactate released into the medium has been shown to be a valid measure of glycogenolysis [15]. The counts released into the medium were furthermore inhibited to the same extent each time the experiments were performed, indicating full inhibition of glycogenolysis.…”
Section: Resultsmentioning
confidence: 99%
“…The T-state is also a better substrate for protein phosphatase-1, the enzyme responsible for the inactivation of GPa to GPb by dephosphorylation. It has been shown that the glucose analogue N-acetyl-β-glucopyranosylamine (1-GlcNAc), which also binds to the glucose binding site, is a much more potent inhibitor of GPa than glucose [14,15]. Moreover, glucose and 1-GlcNAc were both able to potentiate the inhibitory action of caffeine on GPa, with 1-GlcNAc being more potent [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 At present, N-acyl-b-D-glucopyranosylamines, N-acyl-N 0 -b-D-glucopyranosyl ureas, glucopyranosylidene-spiro-heterocycles as well as N-and C-glucosylated heterocycles (see Chart 1 for some important representatives of the latter e.g., 1e7, 13e20) belong to the most potent classes of this inhibitor family displaying their activity in or below the low micromolar range against rabbit muscle GPb (RMGPb). 17e19 X-ray crystallographic studies on the binding modes of several of these molecules elucidated their increased binding strengths in comparison to that of D-glucose (K i ¼1.7 and 7.4 mM for the a and b anomers, 20 respectively). Besides the ideal fit of the glucose part of these inhibitors in the active site, the strong binding must be ascribed to the H-bonding capacities of the aglycons as well as van der Waals interactions of an aromatic appendage (if present) in the so-called b-channel of the enzyme.…”
mentioning
confidence: 99%